Foreignization and Domestication of Indonesian Cultural Terms in the Novel Gadis Pantai Translated into English - Putrawan, Gede Eka (Bina Nusantara University, 2018)
The research was aimed at investigating categories of Indonesian cultural terms translated into English, explaining techniques of applied translation, and analyzing foreignization and domestication ideologies applied in the translations of Indonesian cultural terms into English in the novel Gadis Pantai that translated into The Girl from the Coast. This research was conducted through descriptive-qualitative approach. The data were collected through document analysis including content analysis and thematic analysis. The results show that there are five categories of cultural terms identified in the novel which are translated by using 16 techniques of translation, including the applications of single and double techniques of translation. In addition to foreignization and domestication ideologies of translation, it is also revealed that there is also partial foreignization and partial domestication ideologies of translation since some of the Indonesian identified cultural terms are translated through combinations of two different techniques of translation; combinations of source-language- and target-language-oriented techniques of translation. The most frequently-applied ideology of translation is domestication (82,20%), followed by foreignization (9,82%), as well as partial foreignization and partial domestication (7,98%).